2015
DOI: 10.1007/s40516-015-0013-4
|View full text |Cite
|
Sign up to set email alerts
|

Laser Assisted Milling of Ti-6Al-4V ELI with the Analysis of Surface Integrity and its Economics

Abstract: This study presents the experimental evaluation of laser assisted milling (LAML) of Ti-6AL-4V ELI (Ti-64), which is used in the orthopedic industry, by using localized preheating of the workpiece via laser irradiation. Improvements to the machinability of this material with LAML are assessed while considering the surface integrity. Suitable laser heating conditions as well as machining conditions are determined based on temperature prediction modeling. Machinability improvements are shown in terms of tool wear… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
6
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 25 publications
(13 citation statements)
references
References 29 publications
0
6
0
Order By: Relevance
“…In recent years, the material base for LAM has expanded to a wide range including ceramics [93,[104][105][106][107][108][109], high hardness steel [110,111], stainless steel [112], titanium alloys [113,114], nickelbased alloys [115], metal matrix composites [116][117][118][119], glass [120], semiconductors [121], and ceramic matrix composites [122]. The need for components with diverse geometric shapes has pushed the application of LAM from the dominant turning operation to milling [114,[123][124][125] and micromilling [126][127][128][129], drilling [130], orthogonal cutting [131], and grinding [132,133]. Over the years, the LAM field has attracted various research groups in the world and their engagement has advanced the field in various fronts as evidenced by the large number of studies reported every year.…”
Section: Prediction Of Mechanicalmentioning
confidence: 99%
“…In recent years, the material base for LAM has expanded to a wide range including ceramics [93,[104][105][106][107][108][109], high hardness steel [110,111], stainless steel [112], titanium alloys [113,114], nickelbased alloys [115], metal matrix composites [116][117][118][119], glass [120], semiconductors [121], and ceramic matrix composites [122]. The need for components with diverse geometric shapes has pushed the application of LAM from the dominant turning operation to milling [114,[123][124][125] and micromilling [126][127][128][129], drilling [130], orthogonal cutting [131], and grinding [132,133]. Over the years, the LAM field has attracted various research groups in the world and their engagement has advanced the field in various fronts as evidenced by the large number of studies reported every year.…”
Section: Prediction Of Mechanicalmentioning
confidence: 99%
“…Before conducting a machining experiment it is necessary to first determine the proper preheating temperature, because the mechanical strength of a specific material depends on the temperature. If the preheating range of the material is not appropriate, changes in the material properties and phases may occur, and the machining efficiency may be decreased during TAM [5,27]. In this study, the thermal analysis was performed to determine the proper preheating temperature and effective depth-of-cut (DOC) for the experimental materials [12,15].…”
Section: Thermal Analysismentioning
confidence: 99%
“…Surface oxidation occurs at approximately 1100 °C. Therefore, to avoid changing the crystal grain during the preheating and machining of Ti-6Al-4V, the proper preheating temperature of Ti-6Al-4V was set to 600 °C in this study [27,28].…”
Section: Thermal Analysismentioning
confidence: 99%
“…is has been conducted with different geometrical changes in tool edge radius and heating effects. e laser assisted milling does not influence the specimen characteristics or properties and that was limited to a shallow layer on the peripheral of the work piece that was machined by LAML [7]. Paper [8] has discussed that the total elastic deformation can be calculated in face milling operation which can be identified through the tool flank wear as the major root cause of increasing the elastic deformation.…”
Section: Introductionmentioning
confidence: 99%